The Effect of Silica Added on Large Surface Area Of Nanocrystalline Titania - Tanakulrungsank, Waraporn; Tienkaew, Sornnarong; Praserthdam, Piyasan (Frontiers in Engineering Innovation Research, 2002)
Nanocrystalline titania was obtained from the glycothermal reaction of titanium (IV) tetra-tert-butoxide in 1,4-butanediol solution. An appropriate amount of tetraethyl orthosilicate having Si/Ti ratio of 0 to 0.5 was added into the solutions before taking place of the reaction. The crystallization reaction was conducted in an autoclave under nitrogen atmosphere and a reaction temperature of 300 degree celsius for 2 hours. The product was then calcined at various temperatures from 300 to 1000 degree celsius. The XRD patterns of the titania products obtained revealed that all the products had the anatase structures. This result indicated that addition of small amount of tetraethyl orthosilicate in the titania provided significantly increasing of the BET surface area and reducing the crystallite sizes, and that the peak intensities were not affected by the tetraethylorthosilicate content in the reaction mixture. These results also suggested that addition of silica causes the anatase-rutile phase transformation to shift markedly toward higher temperatures. However, addition of silica over the proper limit will result in the presence of the amorphous phase leading to drastic decrease of thermal stability of the titania product. In this work, the functional group of the product surface was identified using FT - IR spectroscopy in order to observe this effect.